Anti-synthetase syndrome presenting as cryptogenic organizing pneumonia - Haydour, Qusay (Elsevier, 2012)
Interstitial lung disease (ILD) is a unique group of lung diseases that can be associated with inflammatory conditions, such as polymyositis-dermatomyositis (PM-DM). Presentation of PM-DM with ILD is not uncommon but clinical and radiological features can be similar to other conditions (e.g. atypical pneumonia) and can be challenging to diagnose. Delayed diagnosis of PM-DM can be associated with progression of pulmonary involvement and potentially increase morbidity. We report a patient presenting with pulmonary symptoms who had positive anti-Jo-1 antibodies and cryptogenic organizing pneumonia features on biopsy, which is a rare reported finding.